Mobilization for peace: analyzing religious peace activism - Vüllers, Johannes (Conflict management and peace science, 2021)
Under what conditions do religious groups engage in peace activism? Religious groups engage in peace activism if the associated costs are low and they compete with either conflict party over the interpretation of their religious content concerning war and peace. Peace activism is a promising action as peace activists maintain their positive self-evaluation. I introduce a novel dataset of peace activism for 511 religious groups in 128 countries from 1990 to 2008. Conditional fixed effects and logistic models support my hypotheses. The findings highlight the role of rational considerations in the decision to conduct peace activities by representatives of religious groups.